Splenectomy in Pregnant Patient with Sickle Beta-Thalassemia - Adel F. Al-Marzouki; Ayman Zahim; Lenah Alhazmi; Shahad Amro O. Almughamisi; Murad Aljiffry (Journal of Applied Hematology)
Pregnancy in women with sickle cell disease (SCD) poses a high risk to both maternal and fetal health due to increased metabolic demands, blood viscosity changes, and the potential for severe complications such as splenic sequestration crises. Effective management requires a multidisciplinary approach involving hematologists, obstetricians, and surgeons to optimize outcomes. This case report presents the successful management of a pregnant woman with sickle beta thalassemia who developed a sequestration crisis and underwent laparoscopic splenectomy, preventing further complications and improving both maternal and fetal health. A 37-year-old primigravida at 19 weeks gestation, with a history of sickle beta thalassemia diagnosed at the age of one, presented with acute left hypochondriac pain. Examination revealed marked splenomegaly (18 cm below the costal margin) and a live singleton fetus. Laboratory findings confirmed a sequestration crisis, and the patient was admitted for close monitoring. Imaging studies, including ultrasound and MRI, confirmed splenomegaly (24.5 cm) with infarctions. Given the severity of her condition, a multidisciplinary team recommended laparoscopic splenectomy to prevent recurrent crises and optimize pregnancy outcomes. The patient received blood transfusions preoperatively and underwent successful laparoscopic splenectomy, with no postoperative complications. She received vaccinations for meningococcus, pneumococcus, and Haemophilus influenzae type B. At 36 weeks of gestation, she was re-admitted for induction of labor due to cholestasis and delivered a healthy 2.5 kg infant with a good Apgar score. The postpartum period was uneventful, and both mother and child remained stable. This case highlights the importance of early intervention and a multidisciplinary approach in managing pregnant women with sickle beta thalassemia. Laparoscopic splenectomy proved to be a safe and effective option in preventing recurrent sequestration crises and optimizing maternal and fetal outcomes. Blood transfusion strategies, careful perinatal monitoring, and multidisciplinary collaboration are essential in ensuring favorable pregnancy outcomes in women with SCD. Future recommendations include early genetic counseling, close antenatal monitoring, and individualized treatment strategies to mitigate complications associated with sickle beta thalassemia during pregnancy.